Environmental health hazards of e-cigarettes and their components: Oxidants and copper in e-cigarette aerosols. (March 2015) - Lerner, Chad A.; Sundar, Isaac K.; Watson, Richard M.; Elder, Alison; Jones, Ryan; Done, Douglas; Kurtzman, Rachel; Ossip, Deborah J.; Robinson, Risa; McIntosh, Scott; Rahman, Irfan
Abstract: To narrow the gap in our understanding of potential oxidative properties associated with Electronic Nicotine Delivery Systems (ENDS) i.e. e-cigarettes, we employed semi-quantitative methods to detect oxidant reactivity in disposable components of ENDS/e-cigarettes (batteries and cartomizers) using a fluorescein indicator. These components exhibit oxidants/reactive oxygen species reactivity similar to used conventional cigarette filters. Oxidants/reactive oxygen species reactivity in e-cigarette aerosols was also similar to oxidant reactivity in cigarette smoke. A cascade particle impactor allowed sieving of a range of particle size distributions between 0.450 and 2.02 μm in aerosols from an e-cigarette. Copper, being among these particles, is 6.1 times higher per puff than reported previously for conventional cigarette smoke. The detection of a potentially cytotoxic metal as well as oxidants from e-cigarette and its components raises concern regarding the safety of e-cigarettes use and the disposal of e-cigarette waste products into the environment. Graphical abstract: Highlights: E-cigarettes disposal is associated with environmental health hazard/pollution. Oxidants associated with electronic cigarette components and aerosols. Metal copper and nanoparticles detected in electronic cigarette aerosols. Environmental disposal of e-cigarettes components must be regulated with guidelines. Abstract : An electronic cigarette with disposable cartomizer exhibits oxidant reactivity similar to conventional cigarettes and releases copper and other particles associated with its aerosols.